The Implementation of Criterion Referenced Test Approach in Analysis of Student Learning Outcomes at Madrasah Ibtidaiyah - Hadi, M Akmal Binashril; Saputra, Prayoga; Imamah, Anisul; Maisarah, Imas (LPPM Universitas KH.A. Wahab Hasbullah, 2024)
Criterion Referenced Test (PAP) establishes specific standards that students must meet, providing objective evaluations and helping teachers identify which students need remedial support. PAP ensures that all students achieve the required basic competencies. This research describes the application of PAP in analysing Arabic language scores at the Madarah Ibtidaiyah level. Utilizing a qualitative approach with descriptive research, data was collected through unstructured interviews with the school principal and Arabic teacher, as well as observations of student grades. Data analysis involved organizing data by research objectives and interpreting findings accordingly. The study found that PAP facilitates teachers in conducting grade corrections or remedial actions when students fail to meet the set criteria, which is a minimum of 33% or a grade C. The student’s raw Arabic scores are converted to a letter scale, revealing cases where students did not meet the minimum score, necessitating remediation. At MI Miftahul Huda, PAP is used with a letter scale conversion to evaluate grade 4 students' Arabic language performance, with a minimum criterion set at 55% (grade C). This approach simplifies the implementation of remedial measures for students not achieving passing grades and proves effective in tracking student progress.